Reefer madness : sex, drugs, and cheap labor in the American black market - Schlosser, Eric. (Boston : Houghton Mifflin, 2003)
Reports on America's "shadow" economy of illegal drugs, pornography, and illegal migrant workers, arguing that these underground industries continue to grow with government intervention.
Underground -- Reefer madness -- In the Strawberry Fields -- Empire of the obscene -- Out of the underground.
"1147214, 76264"--P. [4] of cover.
Includes bibliographical references (p. 284-292) and index.
Keywords: Informal sector (Economics) -- United States -- Case studies; Black market -- United States -- Case studies; Marijuana abuse -- United States; Migrant agricultural laborers -- California; Illegal aliens -- California; Sex industry -- United States